Parcela digital agroclimatica – Datos de Clima (CUNORI, Guatemala) - Ramos Solorzano, Gresia Dalal; Lizarazo Torres, Miguel Angel; Jimenez Rodas, Daniel Ricardo; Estrada Vargas, Oscar Hernan (2025)
The agroclimatic dashboard provides access to key climate variables, including precipitation, air temperature, relative humidity, dew point, and vapor pressure deficit, generated from in situ monitoring. This information supports local-level decision-making by enabling users to plan and manage critical agricultural activities such as planting dates, fertilization schedules, and crop management practices. With the support of the local partner Centro Universitario de Oriente (CUNORI), the dashboard is publicly available through the SIINTET platform, facilitating open access to agroclimatic information for a wide range of users. These include farmers, students and faculty from CUNORI, members of the Local Agroclimatic Technical Committee, field technicians, and the general public. By providing timely, locally relevant climate data in an accessible format, the dashboard contributes to more informed agricultural decision-making and strengthens climate resilience in vulnerable contexts.